The Relationships among Service Quality, Customer Satisfaction, and Customer Loyalty in Library Services - Wantara, Pribanus (International Journal of Economics and Financial Issues, 2015)
The purpose of this study is to investigate the effects of service quality, customer satisfaction, and customer loyalty in the library of Trunojoyo University. In total, 204 participants students participated in this research. Questionnaires were used for data collection. Additionally, we employed the Structural Equation Modeling (SEM) method to test the causal relationship model. The results showed that the Ï‡2 was 82.666 (degrees-of-freedom [df] = 62), and the overall goodness of fit index (GFI) was 0.943, indicating an empirically good fit with the model. The results of the study indicate that service quality and customer satisfaction are significantly and positively related to customer loyalty. Student satisfaction has found to be an important mediator between service quality and student loyalty. A clear understanding of the postulated relationships among the studied variables might encourage the library to figure out appropriate course of action to gratify students by providing better services in order to create a loyal customer. Keywords: Service Quality; Customer Satisfaction; Customer Loyalty; Library JEL Classifications: M2; M3